2022
DOI: 10.1039/d2cp00169a
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the RBD mutations in the SARS-CoV-2 omicron: from spike opening to antibody escape and cell attachment

Abstract: We computationally investigated the role of the Omicron RBD mutations on its structure and interactions with surrounding domains in the spike trimer as well as with ACE2. Our results suggest...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Using the replica-exchange MD simulations with solute tempering of selected surface charged residues, the conformational landscapes of the full-length S protein trimers were investigated, unveiling previously unknown cryptic pockets and the meta-stable intermediate states [57]. A number of computational studies employed atomistic simulations and binding energy analysis to examine the interactions between the S-RBD Omicron and the ACE2 receptor [58-62]. All-atom MD simulations of the S Omicron trimer and the Omicron RBD–ACE2 complexes suggested that the Omicron mutations may have evolved to inflict a greater infectivity using a combination of more efficient RBD opening, the increased binding affinity with ACE2, and optimized capacity for antibody escape [58].…”
Section: Introductionmentioning
confidence: 99%
“…Using the replica-exchange MD simulations with solute tempering of selected surface charged residues, the conformational landscapes of the full-length S protein trimers were investigated, unveiling previously unknown cryptic pockets and the meta-stable intermediate states [57]. A number of computational studies employed atomistic simulations and binding energy analysis to examine the interactions between the S-RBD Omicron and the ACE2 receptor [58-62]. All-atom MD simulations of the S Omicron trimer and the Omicron RBD–ACE2 complexes suggested that the Omicron mutations may have evolved to inflict a greater infectivity using a combination of more efficient RBD opening, the increased binding affinity with ACE2, and optimized capacity for antibody escape [58].…”
Section: Introductionmentioning
confidence: 99%
“…In silico modelling of the spike protein RGD site (403–405) located with the receptor-binding domain (RBD) has predicted numerous points of contact with its putative integrin receptor, αVβ3 [ 1 ]. It has been proposed that select mutations within SARS-CoV-2 variants of concern enable a more wide-open RBD, thereby increasing the likelihood of host–virus recognition [ 11 ]. We performed ELISA-based assays to confirm the direct binding between integrin αVβ3 and spike protein of wild-type, Delta (B.1.617.2), and Omicron (B.1.1.529) in the presence or absence of the cyclic RGD peptide compound Cilengitide and neutralizing monoclonal antibodies which target the active site of the αVβ3 integrin or the β3 subunit.…”
Section: Resultsmentioning
confidence: 99%
“…81 Computer simulations of the S Omicron RBD structures and complexes with ACE2 detailed the molecular determinants of the enhanced interfacial interactions mediated by the Omicron mutational sites. 82, 83 Recent insightful evolutionary analysis 84 suggested that the mechanisms underlying emergence of the Omicron variant involves multiple fitness trade-offs including balancing between immune escape 8587 and binding affinity for ACE2 proteins 33, 55, 56 and between the requirements to switch to the RBD-up configuration for ACE2 recognition and the increased stabilization of the closed form that prevents binding of neutralizing antibodies. 5988…”
Section: Introductionmentioning
confidence: 99%
“…81 Computer simulations of the S Omicron RBD structures and complexes with ACE2 detailed the molecular determinants of the enhanced interfacial interactions mediated by the Omicron mutational sites. 82,83 Recent insightful evolutionary analysis 84 suggested that the mechanisms underlying emergence of the Omicron variant involves multiple fitness trade-offs including balancing between immune escape [85][86][87] and binding affinity for ACE2 proteins 33,55,56 and between the requirements to switch to the RBD-up configuration for ACE2 recognition and the increased stabilization of the closed form that prevents binding of neutralizing antibodies. Despite of the rapidly growing body of computational studies of the S Omicron proteins the specific regulatory roles of individual Omicron mutations remain unclear, and the potential mechanism underlying a cooperative cross-talk between mutational sites has not been examined at the atomistic level.…”
Section: Introductionmentioning
confidence: 99%